2021
DOI: 10.1108/ijebr-11-2020-0744
|View full text |Cite
|
Sign up to set email alerts
|

Exploring firm-level and sectoral variation in total factor productivity (TFP)

Abstract: PurposeThe objective of the study is to identify and explore factors affecting the productivity of companies in the Czech Republic with a focus on the role of firm size, firm age, indebtedness and long-term negative equity, efficiency of assets usage, liquidity, legal form, location and sector affiliation.Design/methodology/approachThe study utilizes a large unbalanced panel dataset of 91,257 firms (548,998 observations in total) covering the period 2000–2019. The dependent variable, i.e. total factor producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 119 publications
1
11
0
Order By: Relevance
“…We further included a quadratic term of firm age in Supplementary Table 2 in supplementary materials. Consistent with Dvouletý and Blažková (2021), we find that half of the sample countries show a non‐linear U‐shaped relationship between firm age and TFP, whereas the other coefficients are not substantially affected.…”
Section: Heterogeneous Effectssupporting
confidence: 90%
“…We further included a quadratic term of firm age in Supplementary Table 2 in supplementary materials. Consistent with Dvouletý and Blažková (2021), we find that half of the sample countries show a non‐linear U‐shaped relationship between firm age and TFP, whereas the other coefficients are not substantially affected.…”
Section: Heterogeneous Effectssupporting
confidence: 90%
“…The phenomenon where the productivity level of smallscale manufacturing industries is higher than the productivity of largescale enterprises is also found in several countries. For example, a Czech study showed that firms with fewer workers had higher levels of productivity (Dvouletý, O. and Blažková, I., 2021). The results of similar studies in India and Vietnam suggest that smaller firms tend to be more productive than the bigger ones.…”
Section: Resultsmentioning
confidence: 99%
“…Individual countries have undergone a similar transformation of their economic systems, and the development of their national economies is based on similar roots. In the conditions of the Czech Republic, Dvoulety and Blazkova (2021, pp. 1526-1547 dealt with this issue.…”
Section: Discussionmentioning
confidence: 99%